Task effects on tactile temporal order judgments: when space does and does not matter. - Roberts, R; Humphreys, G (2008)
The ability to report the temporal order of 2 tactile stimuli (1 applied to each hand) has been shown to decline when the arms are crossed over compared with when they are uncrossed. However, these effects have only been measured when temporal order was reported by stimulus location. It is unknown whether this spatial manipulation of the body affects all tactile temporal order judgments (TOJs) or only those judgments that are spatially defined. The authors examined the effect of crossing the arms on tactile TOJs when stimuli were identified by either spatial (location) or nonspatial (frequency or duration) attributes. Spatial TOJs were significantly impaired when the arms were in crossed compared with uncrossed postures, but there was no effect of posture when order was judged by nonspatial attributes. Task-dependent modulation of the effects of posture was also evident when response complexity was reduced to go/no-go responses. These results suggest that crossing the arms impairs tactile localization and thus spatial TOJs. However, the data also suggest that localization is not a necessary precursor when temporal order can be computed by nonspatial means.